Analisis Pengelolaan Koperasi Unit Desa (KUD) dalam Meningkatkan Kesejahteraan Anggota: Studi pada Masyarakat Desa Lubuk Mandrasah Kabupaten Tebo Perspektif Ekonomi Islam - Rino Hariyansyah; Titin Agustin Nengsih; Ahmad Syahrizal (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
There are two issues studied in this thesis, namely: the management of Village Unit Cooperatives in improving the welfare of members in Lubuk Mandarsah Village, Tebo Regency and the management of Village Unit Cooperatives from a sharia economic perspective. The aim of this research is to determine the management of Village Unit Cooperatives in improving the welfare of members in Lubuk Mandarsah Village, Tebo Regency and to determine the management of Village Unit Cooperatives from a sharia economic perspective. To reveal this problem in depth and comprehensively, researchers used a qualitative approach by collecting data using observation, interviews and documentation. The data analysis technique used is field analysis using an interactive model including data reduction, data display, data verification. From the research results, it can be concluded that: In the management of the Village Unit Cooperative in Lubuk Mandarsah Village, Tebo Regency, 4 (four) cooperative management functions are implemented, namely: planning, organizing, acting, and monitoring. controlling). There are business units such as supermarkets, convenience stores, savings and loans, agricultural production facilities, and the provision of fertilizer which are solutions for the community according to their individual interests. In the management of the Village Unit Cooperative in Lubuk Mandarsah Village, according to an Islamic economic perspective, namely using the principle of shura' (deliberation) in every decision making, and also using the principle of ta'awun (mutual assistance) in the Village Unit Cooperative which has been implemented but equated with the principle of mutual cooperation.